A Phylogenetic View on the Role of Glycerol for Growth Enhancement and Reuterin Formation in Limosilactobacillus reuteri - Zhang, Zhihong; Wang, Kaiming; Oh, Jee-Hwan; Zhang, Shenwei; van Pijkeren, Jan-Peter; Cheng, Christopher C.; Ren, Dayong; Wei, Hua; Gänzle, Michael G.; Walter, Jens (Frontiers in Microbiology, 2020)
Lineages within the species Limosilactobacillus reuteri have specialized to various hosts and their genomes reflect these adaptations. The pdu-cbi-cob-hem gene cluster is conserved in most human and poultry isolates but is infrequent in rodent and porcine isolates. This gene cluster confers the transformation of glycerol into 3-hydroxy-propionaldehyde (reuterin), which can either be secreted and function as precursor of the antimicrobial compound acrolein or serve as an electron acceptor that enhances the organisms’ growth rate. However, it remains unclear which of these two functions is more relevant for L. reuteri evolution and ecology. Here we characterized the effect of glycerol on growth rate and reuterin formation in L. reuteri strains across different phylogenetic lineages during growth on ecologically relevant carbohydrates. We further evaluated the innate reuterin resistance among these strains to infer a possible role of reuterin in the evolution of strains. Results revealed that the poultry/human lineage VI strain, L. reuteri DSM 17938 shows more growth enhancement through glycerol and greater capacity for reuterin production on glucose and maltose as compared to human lineage II strains. Interestingly, reuterin production in lineage II strains was significantly elevated on raffinose and lactose, reaching levels similar to DSM 17938. On all carbohydrates tested, reuterin production occurred during the exponential growth phase and became undetectable during the stationary growth phase. The amount of reuterin produced was sufficient to inhibit E. coli, suggesting that it could be ecologically relevant, but the resistance towards reuterin among L. reuteri strains was highly variable and, for the most part, unrelated to the strain’s capacity for reuterin production. Overall, the findings suggest differences in the substrate-specific regulation of the pdu cluster in L. reuteri lineages that might be reflective of their ecological niches, e.g. chicken foregut versus human infant and adult large intestine. Such information can inform future studies on the ecology of L. reuteri and guide the development of synbiotic applications to improve the therapeutic use of this species.